Pressure Settlement Behaviour and Bearing Capacity of Asymmetric Embedded Plus Shaped Footing on Layered Sand - Rawat, Priyanka; Dutta, Rakesh Kumar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the present numerical study was to analyse the pressure settlement behaviour and bearing capacity of asymmetric plus shaped footing resting on loose sand overlying dense sand at varying embedment depth. The numerical investigation was carried out using ABAQUS software.
Keywords: granulated blast furnace slag; soil stabilization; settlement; shaped footing; numerical investigations; żużel wielkopiecowy granulowany; stabilizacja gruntu; osiadanie; ława fundamentowa; badania numeryczne